The written competence in spanish curriculum subjects. Academic texts compositions in teachers training: The written competence in subjects of the curriculum (Revista de Investigaciones Universidad del Quindío, 2020)
This research aimed to optimize the teaching and learning process of writing skills in students of two subjects in the curriculum of Spanish and literature, by designing and implementing an intervention proposal for the production of academic texts (Expositive-explanatory and argumentative) aimed at students in the fifth and ninth semesters of the bachelor’s degree in Literature and Spanish Language from the University of Quindío which sought to influence the development of written competence. The research is qualitative based on the Elliott method (2000) on Research-Action-Participation (IAP). In conclusion, it is noted that teachers in training manage to planning, producing, reviewing, rewriting, editing and disseminate texts in their subjects, starting from the implementation of the proposed strategies, which has a positive effect on their preparation as teachers and benefits the development of communicative competence.
Keywords: Communicative competence; written competence; strategies; academic texts